ALGORITHM OF DIAGNOSTICS AND TREATMENT OF AN AGE-RELATED MACULAR DEGENERATION AT PATIENTS WITH CHRONIC PERIPHERAL UVEITIS - Yu. I. Khoroshikh; O. I. Krivosheina; Ye. V. Melekhin (Бюллетень сибирской медицины)
The results of clinical trial of various approaches in treatment the exudative forms of macular degenerations, including age-related, against chronic slow intensity inflammatory process on the extreme retinal periphery of an eye are described in represented material. There were 91 patients (105 eyes) in the research with different types of an exudative macular degeneration. The general criteria of inclusion were: age of 18–80 years old, complaints to discomfort in eyes, a spot before an eye, distortions and decrease in the central sight, ophthalmoscopic symptoms of hypostasis in the central and peripheral areas of a retina. It is analyzed the general criteria of diagnostics and treatment of the disease in the article. Considering defeat of the chorioretinal structures located near the ora serrata at persons of young and advanced age. Practical recommendations to a choice of methods of diagnostics and treatment of various clinical and morphological forms of the disease are made. Screening methods of identification of patients with the peripheral uveitis are offered. The scheme of risk calculation of development the macular pathology at persons with changes on the extreme periphery of a retina, that can be used as a method of prevention of development predictively adverse of “wet" forms of an age-related macular degeneration, by means of timely sparing treatment at patients with chronic inflammatory diseases of eyes is given.